Pulmonary nodules and primary Sjögren syndrome: a case report - Rigoni, Sofia; Lanati, Anna; Cirimele, Francesco; Chetta, Alfredo Antonio (Acta Biomedica Atenei Parmensis, 2023)
Primary Sjögren syndrome (pSS) is a systemic autoimmune disorder that principally affects the exocrine glands but can also affect systemic or extra-glandular sites. Approximately 65-80% of patients with Sjogren's demonstrate pulmonary involvement at the CT scan and pulmonary nodules (PNs) can be encountered as a common finding.We present the case of a 49-year-old woman admitted to the emergency department for chest pain and fever. The patient was diagnosed with pSS fourteen years prior and had never taken therapy or followed regular check-ups. At the HRTC were found PNs that were studied trough a CT-PET and a needle biopsy via CT guidance, which showed diffuse large B cell lymphoma.This case report underlies the importance of check-ups and the need for a multidisciplinary approach in the care of Sjögren’s syndrome patients.